2020
DOI: 10.1186/s42506-020-0035-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to childbearing intentions among women: a cross-sectional study in health centers, Saveh, Iran

Abstract: Background: One of the most important demographic challenges over the recent three decades in the world has been a significant fall in the fertility rate. This study aimed to investigate factors related to childbearing intentions among a sample of Iranian women. Methods: A cross-sectional study of a sample of Iranian married women attending 8 centers in Saveh was conducted in 2015. A total of 483 married women 15-49 years old participated in this study. A questionnaire was used to collect data about demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 25 publications
8
28
1
Order By: Relevance
“…Results indicated that family affluence is more influential for Chinese students than for German students when thinking about having a child now, in that wealthier Chinese students were less likely to want to have a child than less wealthy Chinese students. Having a partner was associated with a higher child wish in both Chinese and German female students, consistent with past research from the middle (23) and far east (25). Age showed an interesting effect on child wish of female students.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results indicated that family affluence is more influential for Chinese students than for German students when thinking about having a child now, in that wealthier Chinese students were less likely to want to have a child than less wealthy Chinese students. Having a partner was associated with a higher child wish in both Chinese and German female students, consistent with past research from the middle (23) and far east (25). Age showed an interesting effect on child wish of female students.…”
Section: Discussionsupporting
confidence: 90%
“…When asked to list factors in their decision to postpone fertility, women in Italy and Spain name changing norms, increased optimism about fertility, as well as economic and social factors as weighing into their decisions to postpone fertility (22). Women in Iran are more likely to express child wish when they are experience higher social support and are in stable marriages (23). In Poland, women who are reluctant to have children are influenced mainly by emotional factors, and men who do not have children are influenced by childrearing values and expectations of satisfaction.…”
Section: Predictors Of Childbearingmentioning
confidence: 99%
“…These beliefs and the values that are intended for them are combined and together, in general, produce a positive or negative attitude toward childbearing. The impact of attitudes on childbearing intention and behavior has been repeatedly demonstrated in both studies conducted in Iran[ 1 8 14 ] and in other countries. [ 9 11 16 21 ] Of course, it should be noted that beliefs and attitudes can be different in various societies and change over time.…”
Section: Discussionmentioning
confidence: 96%
“…[ 10 ] One of the factors affecting childbearing, especially in Iranian Society, which has been proven in several studies, is social support. [ 13 14 15 ] Therefore, in the present study, we decided to add this concept to the TPB and extend it, and consequently, the extended TPB (ETPB) was used as a conceptual framework for the study.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the effect of age is more robust in the wife's age (Zito & Constantine, 2016). Biologically, age is closely related to fertility in reproductive function, especially in women (Araban, Karimy, Armoon, & Zamani-Alavijeh, 2020).…”
Section: Discussionmentioning
confidence: 98%